Unnatural London: the Metaphor and the Marvelous in China Mieville's Perdido Street Station - Abreu, Alexandre Veloso de (Scripta, 2018)
This paper explores allegorical and unnatural elements in China Miéville’s novel Perdido Street Station, starting with a parallel between the fictional city New Crobuzon and London. Fantasy literature examines human nature by means of myth and archetype and science fiction exploits the same aspects, although emphasizing technological possibilities. Horror is said to explore human nature plunging into our deepest fears. We encounter the three elements profusely in the narrative, making it a dense fictional exercise. In postclassical narratology, unnatural narratives are understood as mimetical exercises questioning verisimilitude in the level of the story and of discourse. When considered unnatural, narratives have a broader scope, sometimes even transcending this mimetical limitation. Fantastical and marvelous elements generally strike us as bizarre and question the standards that govern the real world around us. Although Fantasy worlds do also mirror the world we live in, they allow us the opportunity to confront the model when physically or logically impossible characters or scenes enhance the reader’s imagination. Elements of the fantastic and the marvelous relate to metaphor as a figure of speech and can help us explore characters’ archetypical functions, relating these allegorical symbols to the polis. In Miéville’s narrative, such characters will be paralleled to inhabitants of London in different temporal and spatial contexts, enhancing how the novel metaphorically represents the city as an elaborate narrative strategy.